Yesus Sebagai Yang Sulung Lebih Utama Dari Yang Diciptakan - Yosef Yunandow Siahaan (Jurnal Teologi dan Pelayanan Kerusso, 2021)
Throughout the history of the church, from the early Church to the present, Christology has become the main topic of discussion, and it has often led to debates and even polemics for both the Church and those outside the church. The point of a long debate in the field of Christology is about Jesus as a creator or only as a creation. This study investigates this by using theological research, this study uses the exegesis method. The text that will be executed to provide evidence that Jesus was the Creator or creation is Colossians 1:15-20. Jehovah's Witnesses say that this text shows that Jesus was God's First creation. Whereas true Christians actually view this text as saying that Jesus is the Creator. The research used the exegesis method. The results show that Christ is the agent of creation. In building the understanding of the eldest word (Prototokos), it is not allowed to use the isolated text method. There are at least 2 meanings of this word, the first literal meaning is as the first born according to the order of time, and the second, the figurative meaning The eldest means the main, superior. Of course when looking at the context in Colossians 1:16-17, then Christ is not the first born according to chronological order, and comes from creation. Rather, He is the Creator, so it is not surprising that He is supreme or superior to all creation. Abstrak Indonesia Sepanjang sejarah gereja mulai dari Gereja mula-mula hingga kini Kristologi menjadi topik utama diskusi bahkan tak jarang menimbulkan perdebatan bahkan polemik baik bagi Gereja maupun kalangan di luar gereja. Yang menjadi titik perdebatan panjang dalam bidang Kristologi adalah Mengenai Yesus sebagai pencipta ataukah hanya sebagai ciptaan. Penelitian ini menyelidiki hal tersebut dengan menggunakan penelitian Teologi, penelitian ini menggunakan metode eksegesis. Teks yang akan dieksegesa guna untuk memberikan bukti Yesus adalah Pencipa atau ciptaan adalah Kolose 1:15-20. Saksi-saksi Yehuwa mengatakan bahwa teks ini menunjukkan bahwa Yesus adalah ciptaan Pertama dari Allah. Sedangkan Kristen sejati justru memandang teks ini mengatakan bahwa Yesus adalah Pencipta. Penelitian menggunakan metode eksegesis. Hasil penelitian menunjukkan Kristus adalah pelaku penciptaan. Dalam membangun pemahaman kata yang Sulung (Prototokos), tidak boleh menggunakan metode teks terisolasi. Paling tidak ada 2 makna dari kata ini, yang pertama makna literal adalah sebagai yang lahir pertama menurut urutan waktu, dan yang kedua, makna figuratif Yang sulung berarti yang utama, unggul. Tentu ketika melihat konteks dalam Kolose 1:16-17, maka Kristus bukanlah sang pertama lahir menurut urutan waktu, dan berasal dari ciptaan. Melainkan Ia adalah Pencipta, sehingga tidak mengherankan bahwa Ia adalah yang utama atau paling unggul di atas segala ciptaan.